Photosynthesis of Fuji' apple trees protected by two anti-hail nets - Correia, Carlos M. (2017)
The occurence of hail events represents a serious socioeconomic concern for agriculture in several regions ofthe Iberian Península, and theirfrequency and severity may increase in the future in the context of climate change. Given this potential risk, important apple-growing áreas usually subjected to hail storms, as Carrazeda de Ansiães in NE Portugal, will likely need to implement adaptation strategies to minimise potential damages. One technological option is to use over-tree netting to protect fruits and trees from extreme conditions. Moreover, anti-hail nets can also provide additional benefits by reducing plant stress, sunburn and wind speed. The study shows the effects oftwo (grey and black) anti-hail nets applied in mid-July 2016 on leaf gás exchange and chlorophyll fluorescence of apple tree [Malus domestica Borkh. cv. Fuji) at different times between July 22 and September 12. The grey (GAH) and black (BAH) anti-hails nets reduced mean incident photosynthetically active radiation during the leaf gás exchange measurements periods by 12 and 23%, respectively. Although it reduced the incident solar radiation, the BAH net contributed to the improvement of net photosynthetic rate (A) during the summer season, namely during the afternoon period, reducing the degree of photosynthesis depression from the morning to the afternoon. Meanwhile, the plants under the GAH presented higher A than open sky (OS) plants in September, reaching similar values to BAH plants. A closely association was observed between photosynthesis and stomatal conductance, although non-stomatal limitations to photosynthesis, that include changes in photochemical reactions, also occur in OS plants, namely in September. Thus, the use of anti-hail nets on orchards seems to be a suitable solution for the protection of apple trees against hail ensuring lower limitations to photosynthetic activity. Further work is needed to validate these results.